Ideology and Mass Killing: the radicalized security politics of genocides and deadly atrocities - Leader Maynard, Jonathan (Oxford scholarship online, 2022)
In research on 'mass killings' such as genocides and campaigns of state terror, the role of ideology is hotly debated. For some scholars, ideologies are crucial in providing the extremist goals and hatreds that motivate ideologically committed killers. But other scholars are sceptical, contending that perpetrators of mass killing rarely seem ideologically committed, and that rational self-interest or powerful social pressures are more important drivers of violence than ideology. In Ideology and Mass Killing, Jonathan Leader Maynard challenges both these prevailing views, advancing an alternative 'neo-ideological' perspective which fundamentally retheorizes the ideological foundations of violence against civilians and synthesizes an emphasis of ideologies, strategic interests, and social pressures. Integrating research from political science, political psychology, history, and sociology, the book demonstrates that ideological justifications are central to the explanation of mass killings, but in ways that go beyond committed belief. Such ideological justifications revolve, moreover, not around extraordinary political goals or hatreds, but radicalized versions of conventional, widely accepted ideas that underpin the politics of security in ordinary societies across the world. Ideology and Mass Killing then substantiates this account through four contrasting case studies of mass killing-Stalinist repression in the USSR 1930-38, the Allied area bombing of Germany and Japan 1940-45, mass atrocities in the Guatemalan civil war 1978-83, and the Rwandan Genocide in 1994. This represents the first volume to offer a dedicated, comparative theory of ideology's role in mass killing, while also developing a powerful new account of how ideology affects violence and politics more generally.